Zanzīri yā khatṭńāmah da Khwushḥāl Khān Khaṭṭak ijād - Rafīʻ, Habīb Allāh (Da Afghanistān da ʻUlūmo Ak̄ạdmī, 1982)
Analytical study of the special Pushto script called 'zanziri' invented by the well-known Pushto poet Khwushhal Khan Khattah, 17th century, and used by him for secret communication with this family members; previously published in the monthly Kābul mujallah.